Identification of Isocyanate Number on IPDI and TDI Due to Storage Period and Their Impact on Composite Solid Propellant - Pinalia, Anita; Ratnawati, Ratnawati (Department of Chemical Engineering, Faculty of Engineering, Universitas Diponegoro, 2024)
Isocyanate compounds serve as a curing agent in the production of composite propellants, playing a crucial role in determining their characteristics. Due to its high reactivity with moisture, it is essential to determine the isocyanate number of stored samples after a specific duration. The investigation identified the isocyanate number of IPDI and TDI that had been held for 84 and 90 months. The FTIR analysis identified the presence of the NCO group at 2240 cm-1 for TDI and 2243 cm-1 for IPDI samples held for 84 and 90 months. The isocyanate number identification decreased by 1-2% after being stored for six months. This reduction in isocyanate quantity undoubtedly impacts the development of propellant compositions. The reduction in isocyanate content will alter the propellant formulation, leading to propellants with different characteristics due to its impact on the curing ratio (NCO/OH). The curing ratio greatly impacts the mechanical properties of composite propellant.